The Business Process for Receipt and Disbursement of Cash Through Website: Case Study of Riverstone Hotel & Cottage - Syaputri, Diva Wahyu; Riwajanti, Nur Indah; Sumiadji, Sumiadji (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to present an effective business process model to tackle issues related to the cash inflow and outflow cycle at Riverstone Hotel & Cottage. It utilizes Research and Development (R&D) as the research type and follows the ADDIE method, consisting of three stages: analysis, design, and development. The findings suggest the necessity of a website system featuring separate cash inflow and outflow menus for the administrative and front office departments, as well as for the hotel's services (rooms and halls) and expenditures. Implementing real-time management can help reduce processing delays during the calculation and input of room/hall prices across different platforms. Moreover, daily/monthly transaction reports can be conveniently accessed from the provided menu options, eliminating the need for manual recalculations.